2020
DOI: 10.1016/j.psj.2020.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Research Note: Increase of bad bacteria and decrease of good bacteria in the gut of layers with vs. without hepatic steatosis

Abstract: Fatty liver hemorrhagic syndrome ( FLHS ), usually occurring in hens in the late laying period, can lower egg yield and even cause death. Similar to nonalcoholic fatty liver disease in humans, FLHS may begin with simple hepatic steatosis. It is known that gut microbiota is important to the development of nonalcoholic fatty liver disease, but the relationship between FLHS and gut bacteria remains unclear. In this study, bacteria compositions in the ileum and cecum were determined by 16S r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…Further findings indicated that the higher ratio of Firmicutes and Bacteroidetes can induce fat deposition (Ley et al ., 2006 ; Compare et al ., 2016 ; Koliada et al ., 2017 ; Indiani et al ., 2018 ). In addition, recent studies described Sphingomonas as an abundant bacterium in the gut microbiota of chicken (Chen et al ., 2018a ; Li et al ., 2020b ). Another study reported that sphingolipids from Sphingomonas could control different cellular processes, that is migration, apoptosis and proliferation (Bryan et al ., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further findings indicated that the higher ratio of Firmicutes and Bacteroidetes can induce fat deposition (Ley et al ., 2006 ; Compare et al ., 2016 ; Koliada et al ., 2017 ; Indiani et al ., 2018 ). In addition, recent studies described Sphingomonas as an abundant bacterium in the gut microbiota of chicken (Chen et al ., 2018a ; Li et al ., 2020b ). Another study reported that sphingolipids from Sphingomonas could control different cellular processes, that is migration, apoptosis and proliferation (Bryan et al ., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Sphingomonas synthesized sphingosine, which later with fatty acids derivatives formed sphingomyelin, thus reduced fat deposition in the chicken liver. These findings suggested that the abundance of Sphingomonas genus was significantly correlated with hepatic fat metabolism (Li et al ., 2020b ). Microbacterium and Sphingomonas related to lipid metabolism were significantly observed across all chicken embryonic stages, which suggested a significant contribution in the development of gut microbiota for chicken growth (Akinyemi et al ., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were reported previously regarding to those bacteria. Though phylum Proteobacteria included several pathogens, they could degrade the nutrients in the diet and provide suitable environmental support for symbiotic bacteria, and eventually promoted the growth of layers ( Li et al, 2020 ). Shi et al (2019) stated that species in order Oscillospirales , such as Oscillospira , were butyrate producers and negatively related to the F/G ratio in broilers under heat stress.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Sphingomonas was shown to synthesize sphingosine and later formed sphingomyelin with fatty acids derivatives, thus reducing fat deposition in the chicken liver. These findings suggested that the abundance of the Sphingomonas genus was significantly correlated with hepatic fat metabolism ( Li et al, 2020 ). Thus, our results showed that MSM had no negative impact on the gut microbes of kittens.…”
Section: Discussionmentioning
confidence: 97%